On the stability estimation of Wang’s characterization theorem - Januškevičius, Romanas (Lietuvos matematikos rinkinys, 2002)
An important and useful characterization of the Weibull distribution is its lack of memory (of order a) property, i.e., P (X ≥ a√(xa + ya)|X ≥ y ) = P(X ≥ x) for all x, y ≥ 0. The technique commonly employed in proving this characterization is the well-known Cauchy functional equation φ(a√(xa + ya)) = φ(x)φ(y). The stability estimation in this characterization of the Weibull distribution is analysied.